Kansallisesta Ylirajaiseen Kulttuuri, perinne ja kirjallisuus - Hämäläinen, Niina; Karhu, Hanna; Martikainen, Tuomas (Kalevalaseuran vuosikirja, 2023)
Tradition and literature are not held back by borders. Transnationality is, for example, geographic, symbolic, or linguistic movement and action. Different kinds of cultural transitions and migrant traditions are connected with transnationality. Studying the multilingualism of literary texts or diverse cultural identities, transnationality is a prolific angle. In the 102nd Yearbook of the Kalevala Society Foundation, the topics cover for example migration and return migration, material things crossing borders, and places of music culture. At a more theoretical level we are asking how studying transnationality enriches the disciplines with roots in the national sciences.